PENGGUNAAN ALAT PERAGA DALAM PENGAJARAN MATEMATIKA OLEH MAHASISWA PGSD - T Wakiman (Universitas Negeri Yogyakarta, 2000)
This research was to find using visual aid in teaching Abstract out students teacher level of understanding fraction at primary school. The teaching consist ofconcept offraction, relation on fraction, fraction, addition subtraction, multiplication and division of The population of this study was students of D-II Classroom teacher at Faculty of Education of Yogtakarta State University. By using the quota proportional random sample of 25% there were 5l samples in this study. The data was collected by test application to the samples. The data level of understanding in using the visual aid was presented through descriptive analysis in percentages. The fraction equivalent fraction. findings presented in thre categories, which was low, medium and high understanding in using visual aid on teaching fraction..The concluded that: (l) 58,82% students have low understanding and 17,65% have high understanding in teaching concept offraction, (2) Their understanding in relation on fraction, addition, subtraction, multiplication and division in were studlt equivalent fraction, fraction mostly low. The worst was their understanding on equivalent fraction 90,20% were in the low category. The relatively